Emissions of Tetrafluoromethane (CF4) and Hexafluoroethane (C2F6) From East Asia: 2008 to 2019. Issue 16 (16th August 2021) - Kim, Jooil; Thompson, Rona; Park, Hyeri; Bogle, Stephanie; Mühle, Jens; Park, Mi‐Kyung; Kim, Yeaseul; Harth, Christina M.; Salameh, Peter K.; Schmidt, Roland; Ottinger, Deborah; Park, Sunyoung; et al.
Abstract: The perfluorocarbons (PFCs), tetrafluoromethane (CF4 ) and hexafluoroethane (C2 F6 ), are potent greenhouse gases with very long atmospheric lifetimes. They are emitted almost entirely from industrial sources, including the aluminum and rare earth metal smelting industries that emit them as by‐products, and the semiconductor and flat panel display manufacturing industries that use them and vent unutilized amounts to the atmosphere. Despite extensive industrial efforts to quantify and curb these emissions, "top‐down" PFC emission estimates derived from atmospheric measurements continue to rise and are significantly greater than reported process‐ and inventory‐based "bottom‐up" emissions. In this study, we estimate emissions of CF4 and C2 F6 from East Asia, where PFC emitting industries are heavily concentrated, using a top‐down approach (a Bayesian inversion) with high‐frequency atmospheric measurements at Gosan (Jeju Island, South Korea) for 2008–2019. We also compile and analyze the available bottom‐up CF4 and C2 F6 emissions in East Asia from industrial and government reports. Our results suggest that the observed increases in global PFC emissions since 2015 are driven primarily by China's aluminum industry, with significant contributions from Japan's and Korea's semiconductor industry. Our analysis suggests that Chinese emissions occur predominantly from the aluminum industry, although their emissions per production ratio may be improving. Our results for Japan and Korea find significant discrepancies between top‐down and bottom‐up emissions estimates, suggesting that the effectiveness of emission reduction systems (abatement) used in their semiconductor industries may be overestimated. Overall, our top‐down results for East Asia contribute significantly to reducing the gap in the global PFC emission budgets. Plain Language Summary: CF4 and C2 F6, emitted mainly from the aluminum and semiconductor industries, are some of the longest‐lived greenhouse gases known, and among the compounds included under the United Nations Framework Convention on Climate Change in the global effort to reduce greenhouse gas emissions and mitigate climate change. Despite significant progress from both industries in understanding and reducing their emissions over the last 3 decades, the global emissions of CF4 and C2 F6 modeled using atmospheric measurements continue to rise, and are significantly larger than those currently reported by industry and government. In this study, we estimate CF4 and C2 F6 emissions over 2008–2019 in East Asia, where the aluminum and semiconductor industries are heavily concentrated, using a regional inverse model framework combined with measurements at a site in East Asia (Gosan, Jeju Island, South Korea). Our results confirm the dominant role of East Asian emissions in the global budgets of CF4 and C2 F6, led by emissions from China's aluminum industry. Our regional emission estimates are significantly larger than those reported for this region, locating a significant source of the global discrepancy between the reported and atmospheric measurements based emissions for these compounds. We analyze key uncertainties that could lead to these discrepancies. Key Points: CF4 and C2 F6 emissions in East Asia quantified using observations at Gosan (Jeju Island, South Korea) combined with Bayesian inverse model East Asian emissions, significantly underestimated in industry and government reports, drive the global emissions increase since 2015 China's emissions dominated by aluminum industry, and significant uncertainties found in Japan and Korea's semiconductor industry emissions